2016
DOI: 10.1007/s00128-015-1700-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Reproduction, Avoidance Behavior and Oxidative Stress Biomarkers in the Earthworm Octolasion cyaneum Exposed to Glyphosate

Abstract: The massive use of glyphosate (GLY) in several countries has increased the interest in investigating its potential adverse effects in non-target organisms. The aim of the present study was to assess the potential effects in survival and reproduction; avoidance behavior and oxidative stress under short-term (48 h) and subchronic exposures (28 days) to GLY in the earthworm Octolasion cyaneum. After 48 h no significant changes in the behavior was observed. In addition, a lower catalase activity at 498 μg GLY kg(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 23 publications
(22 reference statements)
4
18
0
4
Order By: Relevance
“…Hence, earthworm could migrate between undisturbed and treated areas or might have avoided herbicide-treated within-rows by going into deeper soil layers or burrowing into neighbouring, untreated areas. Such avoidance behaviour among earthworms was reported earlier (Capowiez et al 2003 ; Salvio et al 2016 ). Third, these contrasting effects could also be the result of species-specific responses of earthworms (Pelosi et al 2013 ).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Hence, earthworm could migrate between undisturbed and treated areas or might have avoided herbicide-treated within-rows by going into deeper soil layers or burrowing into neighbouring, untreated areas. Such avoidance behaviour among earthworms was reported earlier (Capowiez et al 2003 ; Salvio et al 2016 ). Third, these contrasting effects could also be the result of species-specific responses of earthworms (Pelosi et al 2013 ).…”
Section: Discussionsupporting
confidence: 83%
“…This could also explain the lack of effects on cocoon production and hatchling numbers, which contradicted a former study where a 50% reduction in hatchling success (Gaupp-Berghausen et al 2015 ) or up to 26% mortality rate (Stellin et al 2017 ) after glyphosate-herbicide application was found. Fourth, earthworm sensitivity to pesticides also varies dependently on different doses and herbicide formulations (C Ma and Bodt 1993 ; Salvio et al 2016 ), and age or development stages of earthworms (Lowe and Butt 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of biomarkers in organism is a reliable tool in environmental pollution studies. It has become a major component of, and alternative to environmental monitoring worldwide (Salvio et al, 2016). In this study, we observed that activities of GST and LDH increased in the three earthworm species exposed to GBH relative to the unexposed.…”
Section: Discussionmentioning
confidence: 64%
“…This species is highly invasive and very successful in the colonization of new areas; it can even outcompete native earthworm species (Kuu and Ivask 2013). Factors related to the success of its invasiveness include strict parthenogenic reproduction, anthropochorous dispersion, high tolerance to extreme soil and climatic conditions, and preference for transformed landscapes, especially man-made grasslands (Brown et al 2006, Hendrix 2006, Pop and Pop 2006, Tiunov et al 2006, Kuu and Ivask 2013, Salvio et al 2016. Octolasion cyaneum (Savigny, 1826) is present in five out of the ten countries of South America: Argentina, Chile, Brazil, Uruguay, and Ecuador (Christoffersen 2011).…”
Section: Introductionmentioning
confidence: 99%